An exploratory study of medical students’ experiences of going on home visits to persons with disabilities within a rural primary health care setting - Van Zyl, Maria Elizabeth (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.